Comprehensive experimental testing and analysis on parabolic trough solar receiver integrated with radiation shield. (15th June 2020) - Wang, Qiliang; Yang, Honglun; Zhong, Shuai; Huang, Yihang; Hu, Mingke; Cao, Jingyu; Pei, Gang; Yang, Hongxing
Highlights: A performance-enhanced parabolic trough solar receiver is manufactured. Indoor heat loss experiment based on heat equilibrium method is conducted. Outdoor thermal efficiency experiment is carried out in two-axis tracking platform. The heat loss of new receiver is reduced by around 28.0%. The thermal efficiency of new receiver is effectively raised by 1.6–4.9%. Abstract: Parabolic trough collectors (PTCs) are the most mature way to harvest high-temperature heat source and widely applied in solar thermal utilizations. Parabolic trough solar receivers as the heat-collecting elements (HCEs) are the key parts of PTC, but face with a knotty problem that is exploding radiative heat loss under high operating temperature, which exerts a significantly negative role on the overall performance of the PTC system. For effectively reducing the heat loss and improving the thermal performance of solar receiver, a structurally optimized HCE with an inner radiation shield was proposed, designed, and manufactured. Furthermore, the indoor heat loss and outdoor thermal efficiency testing were carried out in the Institute of Electrical Engineering, Chinese Academy of Sciences (IEECAS) to validate comprehensive thermal performance of the proposed HCEs. The results show that the radiation shield plays an effective role in reducing the heat loss and improving the thermal efficiency. The heat loss of the proposed HCE is significantly reduced by 28.0% compared to the conventional HCE at the absorber temperature of 550 °C. And the proposed HCE possesses superior performance at high operating temperature and low solar irradiance. In the case of inlet temperature of 350 °C and solar irradiance of 600 W/m 2, the thermal efficiencies of proposed HCE and conventional HCE are 49.4 and 51.8% respectively, and the thermal efficiency of the proposed HCE is effectively enhanced by 4.9%.